2022
DOI: 10.3389/fcimb.2022.899566
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Augments the Quorum Quenching Potential of Cinnamaldehyde In Vitro and Protects Caenorhabditis elegans From Pseudomonas aeruginosa Infection

Abstract: The quorum sensing (QS) circuitry of Pseudomonas aeruginosa represents an attractive target to attenuate bacterial virulence and antibiotic resistance. In this context, phytochemicals harboring anti-virulent properties have emerged as an alternative medicine to combat pseudomonal infections. Hence, this study was undertaken to investigate the synergistic effects and quorum quenching (QQ) potential of cinnamaldehyde (CiNN) in combination with gentamicin (GeN) against P. aeruginosa. The QQ activity of this novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…aeruginosa and S. aureus, which supports the presented findings. , Biofilm formation in P. aeruginosa has been regarded as a crucial virulence feature that contributes to resistance against antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…aeruginosa and S. aureus, which supports the presented findings. , Biofilm formation in P. aeruginosa has been regarded as a crucial virulence feature that contributes to resistance against antimicrobial agents.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular docking analysis demonstrated robust binding interactions between the QS receptors and cinnamaldehyde, confirming its significant potential as a QS modulator. This dual treatment effectively eliminated pre-existing biofilms and suppressed the creation of new biofilms by disrupting the production of EPS ( Chadha et al, 2022 ). Noteworthy, the authors suggested that the synergistic interaction between the drugs can be related to their unique mechanisms of action.…”
Section: Cinnamaldehydementioning
confidence: 99%
“…This renders the bacterial cell more vulnerable as the medications can simultaneously target two separate cellular areas. In addition, cinnamaldehyde efficiently inhibits the QS circuits in P. aeruginosa by reducing the expression of QS genes and preventing the production of AHL molecules ( Shaw and Wuest, 2020 ; Chadha et al, 2022 ). The mentioned function of cinnamaldehyde was attributed to its potent interaction with the QS receptors of P. aeruginosa .…”
Section: Cinnamaldehydementioning
confidence: 99%
See 1 more Smart Citation
“…It also reduces the relative expression of four QS genes (lasI, lasR, rhlI, rhlR) and the biofilm-related gene ndvB [79]. On its side, the combination of cinnamaldehyde with gentamicin represses acylhomoserine lactones production and downregulates the expression of critical QS genes, to substantially diminish pyocyanin, alginate, rhamnolipid, hemolysin, protease, and elastase production, to successfully suppress preformed biofilms and to impair biofilm formation by disrupting EPS production [80].…”
Section: Strategies For Inhibiting Biofilm Formation and Quorum Sensingmentioning
confidence: 99%